PjBL with Kahoot Media on Grade X Students’ Biology Interest at SMAN 1 Wundulako - Gurning, Sonia Sumiarti; Tendrita, Miswandi; Erfina, Erfina (Universitas Sembilanbelas November Kolaka, 2025)
Learning at SMAN 1 Wundulako remains centered on lectures and textbooks. Although media such as PowerPoint and Canva have been used, their utilization has not been optimal. As a result, students tend to be passive and show low learning interest. Therefore, there is a need for innovative learning models and interactive media to enhance students' interest in learning. This study aims to examine the effect of implementing Project-Based Learning assisted by Kahoot media on students’ learning interest in biology. The research employed a quantitative approach with a quasi-experimental method. The research design used was a posttest-only control group design. Instruments used to measure students' learning interest included questionnaires and interview sheets. Data were analyzed using a parametric test, namely the independent sample t-test, at a significance level of 0.05. The results of the hypothesis testing indicate a significant effect of Project-Based Learning assisted by Kahoot media on students’ learning interest in biology among Grade X students at SMAN 1 Wundulako. It can be concluded that the implementation of Project-Based Learning supported by Kahoot media can help improve students’ interest in learning biology in Grade X at SMAN 1 Wundulako.Keywords: Learning Interest, Project-Based Learning, Kahoot-Assisted Media